0117 Impact of Light Exposure during Sleep on Cardiometabolic Function. (27th April 2018) - Mason, I; Grimaldi, D; Malkani, R G; Reid, K J; Zee, P C
Abstract: Introduction: Artificial light exposure is increasingly widespread, particularly at night. Light exposure at night is known to impact circadian rhythms such as melatonin and sleep, and disturbances in these rhythms have been shown to affect cardiometabolic function. As such, the aim of this study was to test the hypothesis that light exposure at night during sleep negatively impacts cardiometabolic outcomes, possibly via disruptions to sleep architecture and melatonin profiles. Methods: Twenty healthy adults 18–40 years of age were randomized into Dark-Dark (DD) or Dark-Light (DL) groups and run in parallel for a three day and two night stay. Participants had 8 hours of sleep opportunity each night starting at habitual bedtime determined from one week of actigraphy with sleep diary. The DL group (n=10, 2 males, ages 26.61 ± 4.64 years, BMI 23.25 ± 3.94 kg/m^2) slept in the dark < 3 lux on Night 1 and slept in overhead room light of 100 lux on Night 2, while the DD group (n=10, 4 males, ages 26.78 ± 5.15 years, BMI 24.25 ± 3.71 kg/m^2) slept in the dark <3 lux on both Nights 1 and 2. Overnight polysomnography and hourly blood sampling for melatonin were collected on both nights. Oral glucose tolerance tests were performed on both mornings following sleep in the dark or 100 lux of light. Repeated measures ANOVA were performed between groups (DL vs. DD) with Day (Day 1 vs Day 2) and Time of Day as within-subject factors. Results: Homeostatic model assessment of insulin resistance values were significantly higher (p<0.05) in the morning following sleep in the light (DL group) compared to sleep in the dark (DD group). This effect was primarily due to increased insulin levels for DL compared to DD group, for which there was a trend for group by day effect (p<0.09). Conclusion: A single night of light exposure during sleep acutely impacts insulin resistance, and chronic overnight exposure may have long-term effects on metabolic function. Support (If Any): This research was supported National Institutes of Health grants 5T32HL7909, P01AG11412, and 8UL1TR000150-05.